Performance of Aged Asphalt Binder Treated with Various Types of Rejuvenators - Munder Bilema; Yusri Bin Aman; Norhidayah Abdul Hassan; Zaid Al-Saffar; Kabiru Ahmad; Kabiru Rogo (Civil Engineering Journal, 2021)
High demand for asphalt binders in road construction verifies the need of finding alternative materials through asphalt pavement recycling. This paper investigated the impact of different rejuvenators on the performance of an aged asphalt binder. Virgin Olive oil, virgin cooking oil, waste cooking oil, virgin engine oil, and waste engine oil were added to a 30/40 penetration grade aged asphalt binder at a fixed oil content of 4% for all types. The wet method was used to blend the rejuvenators and aged asphalt binder. The physical, rheological, and chemical properties of the rejuvenated asphalt binder were evaluated using several laboratory tests which include penetration, softening point, bleeding, loss on heating, storage stability, penetration index, ductility, viscosity, dynamic shear rheometer, and Fourier transform infrared spectroscopy. The outcomes of the physical properties showed that the olive, waste, and virgin cooking rejuvenators can restore the aged asphalt binder to a penetration grade of 60/70. In contrast, the virgin and waste engine oil required a more quantity of oil to rejuvenate the aged asphalt binder. A sufficient amount of rejuvenator could regenerate the (G*/sin δ), (δ°), and (G*) for the aged asphalt binder. The addition of virgin olive and cooking oils in aged asphalt led to a rutting issue. No chemical reactions were observed with the addition of rejuvenators but they give an impact on reducing the oxidation level of the aged asphalt binder. As a result, further research should be performed on waste cooking oil given that it is inexpensive and provides excellent performance results. Doi: 10.28991/cej-2021-03091669 Full Text: PDF